Thermo-mechanical properties of mixed-matrix membranes encompassing zeolitic imidazolate framework-90 and polyvinylidine difluoride: ZIF-90/PVDF nanocomposites - Irina S. Flyagina; E. M. Mahdi; Kirill Titov; Jin-Chong Tan (APL Materials, 2017)
Mixed-matrix membranes are contemporary nanocomposite materials with many potential applications, from liquid and gas separations to chemical sensors and biomedicine. We report fabrication of a metal-organic framework (MOF)-based nanocomposite, combining polyvinylidene difluoride (PVDF) polymer as the matrix and ZIF-90 nanocrystals of up to 30 wt. % filler content. The focus is to establish the processing—microstructure—mechanical property relationships. We reveal the importance for quantifying salient effects of the filler contents: (i) tensile strength degrades beyond 10 wt. % and (ii) mechanical toughness declines due to membrane embrittlement. These are vital mechanical aspects but widely overlooked in the emergent field of MOF membranes and composites.